Special Care Manual (SCM) version 1.0 - Hasan, Haliza; Samsudin, Nurul Nabilah; Abdul Hamid, Nur Mursyidah; Ismail, Nurul Nabiha; Mohd Zainuddin, Nadilla Daleena; Noor Iskandar Hashim, Aimi Najwa; Suhaimi, Fatin; Adnan, Aida Azilah; Muhamad Radzi, Alia (2021)
This Special Care Manual (SCM) Version 1.0 was designed as a manual guide for caring for people with special needs. This manual was designed to be used by the Community-Based Rehabilitation Centre, Kompleks Penyayang in Kuantan, and will be expanded the implementation of the other CBRs for the whole Pahang. This disclosure consisted of 3 parts; Personal Hygiene, Oral Care, and Diet Intake for people with special needs. This version 1.0 was designed as a baseline to develop a digital version by using suitable apps that easy to be used by caregivers of people with special needs.